Characterization of soybean genotypes based on morphological and molecular markers - Niharika Saharia* and Ramendra Nath Sarma (Electronic Journal of Plant Breeding, 2022)
The present investigation was carried out with 38 soybean genotypes during Kharif, 2020. The variability analysis was done using 10 quantitative and 11 qualitative characters. Twenty four SSR markers were used to study genetic relationships among the genotypes based on Jaccard’s coefficient of similarity. The analysis of variance revealed that there were significant variations for yield and yield attributing characters. Plant height, the branches per plant, the pods per plant and seed yield showed the highest coefficients of variability along with high heritability with a genetic advance as percentage of mean. Correlation and path coefficient analyses identified plant height, the branches per plant and the pods per plant traits identified as important traits for yield improvement in soybean. Euclidean distance based on qualitative characters indicated the genotypes DLSb-2 and JS 22-14 are most divergent, while quantitative characters based analysis revealed that the genotypes NRC 128 and TS20-5 are potential for use in breeding. Out of 24 soybean specific SSR primers, 19 were found to be polymorphic. The number of SSR allele per locus ranged from one to three with an average of 1.4 alleles per locus. DNA marker analysis revealed a range of diversity in the experimental materials with few potential markers for diversity analysis due to their high PIC values.